Two new millipede species of the genus Riukiaria (Diplopoda, Polydesmida, Xystodesmidae) endemic to the Ryukyu Archipelago, Japan - Korsós, Zoltán; Nakamura, Yasuyuki; Tanabe, Tsutomu (Zootaxa, 2011)
We describe two new species of the millipede genus Riukiaria from two islands of the Ryukyu Archipelago: R. maculata sp. n. from Tane-ga-shima, northern Ryukyus, and R. mundyi sp. n. from Yonaguni-jima, the southwesternmost member of the Yaeyama Island Group. Both species show the simple forceps-like male gonopod structure typical for the genus, but they are readily distinguishable from other members by their unique color patterns. We have also compiled a list of species in the genus described up to now.